Ethical sensitivity in consumers’ decision-making: The mediating and moderating role of internal locus of control - Toti, Jean-François; Diallo, Mbaye Fall; Huaman-Ramirez, Richard (Journal of business research, 2021)
•The relationships among CES, ethical judgment and ECB are explored are .•The study partially validates the Hunt-Vitell general theory of marketing ethics.•iLOC) positively moderates the relationship between ethical judgment and ethical consumption behavior (ECB).•iLOC mediates the relationship between CES and ECB.•LOC: Internal locus of control; ECB: ethical consumption behavior; CES: Consumers’ ethical sensitivity. Ethical behavior has been a topic of increasing research interest, but only a few studies have examined ethical decision-making through a holistic consideration of ethical consumption. In this paper, we empirically establish the relationship between consumers’ ethical sensitivity (CES), ethical judgment and ethical consumption behaviors (ECB). We also examine the mediating and moderating role of internal locus of control (iLOC) in these relationships, a key factor that could explain individuals’ behaviors but has never been explored through a holistic approach to ethical consumption behavior. Based on data from 684 consumers and a structural equation model, our findings empirically support part of the Hunt-Vitell and Kotler-Zaltman theories, i.e., CES has a direct and positive effect on both ethical judgment and ECB, and ethical judgment positively impacts ECB. Moreover, while iLOC mediates the relationship between CES and ECB, its moderating role is significant only in the relationship between ethical judgment and ECB. This contributes to a better understanding of consumer ethics, with several implications for ethical brand management, at the same time opening up new research avenues for further investigation.